Comparison of Platelet Index in Type 2 Diabetes Mellitus Patients With and Without Diabetic Ulcers - Rahma Yuliana, Putri; Suhariyadi, Suhariyadi; Woelansari, Evy Diah (Devotion : Journal of Research and Community Service, 2025)
Hyperglycaemia is caused by poor insulin production and insulin resistance, which is the beginning of type 2 diabetes mellitus. The blockage of blood vessels caused by this disease is due to the increase in blood sugar levels, which is the cause of diabetic ulcers. As a result, patients are often unaware of their injuries. This research aims to identify differences in platelet indices (MPV, PDW and PCT) in people with type 2 diabetes mellitus who have diabetic ulcers and those who do not. This research uses observational analysis methods and a cross-sectional analysis approach. The independent variable in this study was type 2 diabetes mellitus patients with and without diabetic ulcers, while the dependent variable in this study was the platelet value, consisting of MPV in type 2 diabetes mellitus patients with and without diabetic ulcers of 7,716 fL and 7,837 fL. The mean PCT in type 2 diabetes mellitus patients with and without diabetic ulcers was 0.225% and 0.245%, respectively. The mean PDW in type 2 diabetes mellitus patients with and without diabetic ulcers was 18.825% and 14.237%, respectively. The results of data analysis using unpaired t-test showed a p-value of 0.00 for PDW and 0.002 for MPV, so it was concluded that there were differences in MPV and PDW in type 2 diabetes mellitus patients who had diabetic ulcers and those who did not.